How Does The Bilingualism Improve the Student English Ability: a Discourse Case Study on Higher Education - Cesaria, Anna; Kemal, Edwar; Adnan, Mazlini (ppjbsip, 2023)
In this 4.0 era, the use of English as a mean of communications playing a vital role to work in many parts such as technology, education, communication and many others. It is true that not all people can communicate in English fluently and clearly. Luckily, some people or students especially, use bilingualism to study or learn English. Many of them think by using bilingualism they still can interact or communicate by using English as a mean of interaction. Focus of this research was to find out how the bilingualism improve the English student ability. This research used a descriptive qualitative research. Data were collected by using questionnaire and interview guideline. Data were analyzed by using the content analysis and the theory used was proposed by Hoffman 1991. Population of the research was all of students of English for mathematics consisting 35 students. This research used total sampling for instrument using questionnaire and used purposive sampling for the semi-structure interview. The research shows that bilingualism occur in the classroom interaction such as talking about particular topic, quoting somebody else, being emphatic about something, interjection, repetition used for clarification, expressing a group of identity and intention of clarifying the speech content for interlocutor. From the analysis, it is seen that mostly bilingualism used by the students to study about particular topics such as term, theme and content. The least used by student is on the intention of clarifying the speech content for interlocutor because the students always think that what the people say are true and they don’t know how to express the clarification in English. However, for the English learning, bilingualism has already helped both the lecturers and students to interact and communicate about various topics. It is a good start to introduce English as the foreign language In Indonesian Higher Education where English is still considered as the foreign language.